ENHANCING WORK ENVIRONMENT IN A CREATIVE COMPANY: THE CASE OF PT. XYZ - Safarina, Nadya
PT. XYZ is company that categorized in fashion and craft sub-sectors which produce wooden watches in Indonesia. PT. XYZ encountered some challenges in selling their products due to VUCA era and COVID-19 pandemic situation. In 2020 while facing the pandemic situation, PT. XYZ facing declining sales, difficulties in producing new design, and declin ing result from output’s content feedback and campaigns on social media. In order to survive and improve their performance in this uncertainty era while facing tough competition, creativity is needed. Even though creativity is needed to keep their business thrive, PT. XYZ find it d ifficult to stimulate employees’ creative thinking. In order to keep their business thrive and help company to gain competitive advantage, the company reconsider to improve their employees’ creativity through work environment as the performance of the employees in regard to produce creative output is mainly affected by the condition of the workplace. In regard to workplace creativity, the issues about potential lack of support from the work environment that supports creativity were found at PT. XYZ.